GALILEAN GEOMETRY OF CORRESPONDING SURFACES TO PRODUCTION MODELS IN ECONOMICS - Aydin, M. E.; Sepet, S. A. (Univ Kragujevac, Fac Science, 2015)
In this paper we study the curvature properties of the corresponding surfaces in the Galilean 3-space G(3) to some production models in economics such as the generalized Cobb-Douglas, the generalized ACMS and the Allen production functions. We classify such surfaces of null curvature in G(3).
Keywords: Generalized Cobb-Douglas production function; generalized ACMS production function; Allen production function; Galilean space; Gaussian curvature; mean curvature